Use of Home Remedies and Traditional Medicines for the Treatment of Common Eye Ailments in Pakistan: A Qualitative Study - Khan, Azam Ali, Clare Gilbert, Khabir Ahmad, Mohammad Aman Khan, Mohammad Babar Qureshi, Mohammad Daud (Pakistan Journal of Ophthalmology, 2009)
Purpose: Qualitative studies focusing on the use of home remedies and traditional medicines for eye health are lacking. We explored the use of eye remedies and traditional eye medicines (referred to hereafter as “eye remedies/TEM”) in Pakistan’s Abbottabad district. Material and Methods: We conducted face-to-face key informant interviews with 16 teachers (8 men, 8 women). Participants were asked to list eye remedies/TEM used in their home or in areas where they lived. They were also asked to specify conditions for which each one of them is used. Their responses were noted manually and the interview scripts were translated from Urdu into English. A content analysis of the transcripts was carried out to identify the main themes arising from the interviews. Results: Eye remedies/TEM were popular with the participants and in areas where they lived. 18 eye remedies/TEM were identified, the majority of them being used to treat irritable, red eye. The most frequently mentioned symptom necessitating eye remedies/TEM was burning or itching, followed by redness, watering and pain, and swelling. One participant noted his family uses goat’s milk diluted with water to treat red, dirty and discharging eyes in newborn babies. Other main themes were the use of remedies/TEM particularly surma (kohl) to “sharpen the vision” and to “enhance the appearance of the eyes”. Conclusions: Our study provides evidence of the use of eye remedies/TEM in Pakistan. Future studies should look at the safety and efficacy of these therapies, the frequency of use in a large population and explore if these therapies are used together with, or in place of, conventional medicine. The practice of putting goat’s milk in eyes of newborn babies with red, dirty and discharging eyes must be discouraged.